Prognosis after resection for hepatitis B virus-associated intrahepatic cholangiocarcinoma - Wu, Zhen-Feng (World J Gastroenterol, 2015)
AIM: To investigate the prognostic factors after resection for hepatitis B virus (HBV)-associated intrahepatic cholangiocarcinoma (ICC) and to assess the impact of different extents of lymphadenectomy on patient survival. METHODS: A total of 85 patients with HBV-associated ICC who underwent curative resection from January 2005 to December 2006 were analyzed. The patients were classified into groups according to the extent of lymphadenectomy (no lymph node dissection, sampling lymph node dissection and regional lymph node dissection). Clinicopathological characteristics and survival were reviewed retrospectively. RESULTS: The cumulative 1-, 3-, and 5-year survival rates were found to be 60%, 18%, and 13%, respectively. Multivariate analysis revealed that liver cirrhosis (HR = 1.875, 95%CI: 1.197-3.278, P = 0.008) and multiple tumors (HR = 2.653, 95%CI: 1.562-4.508, P < 0.001) were independent prognostic factors for survival. Recurrence occurred in 70 patients. The 1-, 3-, and 5-year disease-free survival rates were 36%, 3% and 0%, respectively. Liver cirrhosis (HR = 1.919, P = 0.012), advanced TNM stage (stage III/IV) (HR = 2.027, P < 0.001), and vascular invasion (HR = 3.779, P = 0.02) were independent prognostic factors for disease-free survival. Patients with regional lymph node dissection demonstrated a similar survival rate to patients with sampling lymph node dissection. Lymphadenectomy did not significantly improve the survival rate of patients with negative lymph node status. CONCLUSION: The extent of lymphadenectomy does not seem to have influence on the survival of patients with HBV-associated ICC, and routine lymph node dissection is not recommended, particularly for those without lymph node metastasis.